Pharmaceutic guidance to hypertensive patients at USP University Hospital: effect on adherence to treatment - Ana Luiza Pereira Moreira Mori; Joel Claudio Heimann; Egídio Lima Dórea; Márcia Martins Silveira Bernik; Sílvia Storpirtis (Universidade de São Paulo, 2010)
This study was carried out in the outpatient unit of the Teaching Hospital of the University of São Paulo (USP), and studied the impact of an educational program aimed at improving hypertensive patients' compliance to treatment. Seventy five (75) hypertensive patients of both sexes took part in the study which had no age or race discrimination. Participants presented no other concomitant pathology, except obesity, diabetes and dyslipidemia. Forty one patients were allocated to an experimental group (EG). Experimental patients attended lectures on the use of medication and artery hypertension (AH) and received personal pharmaceutical guidance for nine months. The control group (CG) comprised 34 patients who did not attend lectures or receive pharmaceutical advice in this period. The results were assessed by means of serum levels of cholesterol and fractions of tryacylglicerol (TG), urine sodium and potassium, arterial pressure (AP), body mass index (BMI), waist-hip ratio (WHR), and also based on responses to a questionnaire focusing on AH and treatment. Patients who received the guidance showed a greater decrease in AP, TG and WHR, besides an increase of potassium excretion through urine. The experimental group also scored higher on the questionnaires compared to the CG. It was concluded that the educational process, applied under the conditions of the present study, improves clients' clinical response to antihypertensive treatment and should be included in therapeutic strategies of health care services dealing with hypertensive patients. Este trabalho, realizado no ambulatório do Hospital Universitário da USP, estudou a repercussão de um programa educacional visando melhorar a adesão do paciente hipertenso ao tratamento. Participaram do trabalho 75 pacientes de ambos os sexos, sem discriminação de idade ou raça, sem outras patologias concomitantes, exceto obesidade, diabetes e dislipidemia. Quarenta e um pacientes assistiram palestras sobre uso de medicamentos e hipertensão arterial (HA), receberam orientação farmacêutica individualizada durante nove meses e foram denominados grupo experimental (GE); o grupo controle (GC), composto por 34 pacientes não assistiu palestras nem recebeu orientação farmacêutica, neste período. Os resultados foram avaliados por meio de níveis séricos de colesterol e frações, triacil-gliceróis (TG), sódio e potássio urinários, pressão arterial (PA), índice de massa corpórea (IMC), relação cintura/quadril (RCQ), além de respostas a questionário enfocando HA e tratamento. Verificou-se que os pacientes orientados apresentaram maior decréscimo da PA, TG e da RCQ, além de aumento da excreção urinária de potássio e do percentual de acertos em questionários, em relação ao GC. Concluiu-se que o processo educativo, utilizado nas condições deste estudo, melhora a resposta clínica do paciente ao tratamento anti-hipertensivo e deve fazer parte das estratégias terapêuticas de serviços de atendimento a pacientes hipertensos.